Mechanical Properties of Kenaf/Polyester Composites - M.Y, YUHAZRI; P.T, Phongsakorn; I.P, Haeryip Sihombing; A.R., Jeefferie; A. P., Puvanasvaran; A.M, Kamarul; Rassiah, Kannan (IJENS Publishers, 2011)
In this study, the reinforced kenaf fibers using polyester resin composites were processed through vacuum infusion method. Before infusion and reinforced applied, the long kenaf fibers were treated by various concentration of sodium hydroxide(NaOH). The effects of the modification on fiber and also the effect of fiber alkalization on composites then is analyzed for mechanical properties and by using the scanning electron microscopy (SEM). The results showed that the alkalization treatment has improved the mechanical properties of the composites as compared to the composites with untreated kenaf fiber. In addition, a general trend of the mechanical performances of alkalized kenaf fiber composites observed showed increase with the increments of NaOH concentration. In this study, the vacuum infusion method used also offers benefits over hand lay-up method due to the better fiber to resin ratio that resulting in stronger and lighter laminates. By vacuum infusion process, the kenaf-polyester composite manufactured provides an opportunity for replacing the existing materials with a higher strength, low cost alternatives, and environmental friendly